2007
DOI: 10.1080/14767050601036527
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of subsequent delivery after a previous early preterm cesarean section

Abstract: In this small series of women with a previous early preterm cesarean section the VBAC rate was high (61.1%) and the uterine rupture rate was 1.1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 14 publications
1
14
0
1
Order By: Relevance
“…2,3 Birth by caesarean delivery is generally more hazardous than a normal vaginal delivery, and also poses more risks for subsequent pregnancies. 4,5 Therefore, it is hypothesized that prediction of the success rate of induction of labour might lead to a reduction in caesarean delivery and there by its complications. The relation between clinical state of cervix and spontaneous onset of labour has been known for many years.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Birth by caesarean delivery is generally more hazardous than a normal vaginal delivery, and also poses more risks for subsequent pregnancies. 4,5 Therefore, it is hypothesized that prediction of the success rate of induction of labour might lead to a reduction in caesarean delivery and there by its complications. The relation between clinical state of cervix and spontaneous onset of labour has been known for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Several additional studies found no heightened uterine rupture risk after preterm cesarean(13-15), though some studies were limited by relatively small cohort sizes(13, 14). Harper et al compared uterine rupture risk after cesarean delivery before or after 34 weeks of gestation and found no difference in risk among women undergoing a subsequent trial of labor.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest increased risk of subsequent rupture after preterm cesarean delivery, estimating between a 1.6 and 5 fold increase(11, 12), while other studies show no association(13-15). The specific risk for uterine rupture after cesarean delivery at periviability remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However Kwee (2007) and Rochelson (2005) noted that pre-term casearean section, even if a transverse incision, was a risk factor for uterine rupture. Our VBAC rate (82.4%) compares favourably.…”
Section: Midwestern Regional Maternity Hospital Limerickmentioning
confidence: 96%